Therapeutic implication of coenzyme Q10 during statin therapy: pros and cons - Afshin Mohammadi-Bardbori; Mir-Jamal Hosseini (Shiraz University of Medical Sciences, 2015)
Coenzyme Q10 (CoQ10) is a vitamin-like substance, and a natural intermediate of electron transport chain (ETC) of mitochondria which can accepts and donates electrons from complex I to complex II. CoQ10 shares a biosynthetic pathway with cholesterol, therefore it can be a potential target of the widely available lipid-lowering agents. The lipid lowering drugs such as statins, are widely administered to individuals who have high cholesterol levels and potential risk for cardiovascular diseases. Statins do not cause serious adverse effects in human however its long-term administration can cause a variety of myopatic complaints.This article reviews the a) clinical benefits of CoQ10 b) association between administration of statin and CoQ10 deficiency and c) involvement of CoQ10 in statin-associated myopathy.